Why do I feel an Impostor?: The roles of work alienation, cynicism and work insecurity - Velez, M. J.; Junça Silva, A.; Simões, L. M. (Dialogues in Organizational Behavior: Book of Abstracts, 2024)
There is growing evidence in the literature that the Impostor Syndrome has an impact on a broad range of variables in the private and work life. Defined as high-achieving individuals' failure to internalize accomplishments, we aim to expand on the existing research on this phenomenon by exploring its antecedents by analyzing (1) the relationship between within-person fluctuations in work alienation and cynicism and impostor syndrome and (2) between-person variations in work insecurity as a relevant boundary condition of this relationship.